Globalization Of Tourism Industry Toward Culture Of Local Wisdom In The Existance Of Pseudo Traditional Art Case Study of the Commodification of Bengkulu Traditional Arts - Bambang Parmadi; Benardin (Institut Seni Indonesia Denpasar, 2021)
The influence of globalization toward cultural context is a transaction of cultural things through industrial process affected by modernization. Tourism industry is one of the globalizations which produces cultural things to be commercialized financially and purposefully. One of cultural things to be commercialized in the era of globalization is traditional art. The issue coming up is how to develop patterns so that the supporters of traditional art as the subject of local wisdom are maintained, but hopefully it can, on the other hand, accommodate globalization demands, for both economic and sociocultural aspects which have commodified culture? With the aim of synergizing the existence of traditional art as cultural identity of supporters in sociocultural way and the demands of tourism industry that commodify culture, through field research using qualitative method, it can be concluded that. First, commodification of culture is inevitable in the era of 4.0 which develops in modernity, which can be seen from more developed tourism industry. Second, commodification of culture toward local wisdom can actually be solved with some strategies without marginalizing the supporters of the local wisdom and culture. Third, the space of traditional art as cultural identity can be maintained and revitalized from commodification of culture as long as the conceptual pattern can synergize the perception and responses of the supporters with the demands of tourism industry. Forth, one of the most relevant concept to accommodate the demands of commodification of culture is what is known as pseudo traditional art.